Меженнные периоды рек Южного берега Крыма - Тимченко, З.В. (Культура народов Причерноморья, 2014)
Обобщение гидрометрических данных позволяет получить расчётные соотношения для определения гидрологических характеристик рек при отсутствии на них наблюдений. В статье приводятся расчётные соотношения для оценки частоты 30-ти суточных минимальных расходов воды для рек Южного берега Крыма при отсутствии гидрометрических наблюдений. Такие расчёты необходимы при решении различных водохозяйственных задач. Узагальнення гідрометричних даних дозволяє одержати розрахункові співвідношення для визначення гідрологічних характеристик річок при відсутності на них спостережень. У статті наводяться розрахункові співвідношення для оцінки частоти 30-ти мінімальних добових витрат води для річок Південного берега Криму при відсутності гідрометричних спостережень. Такі розрахунки необхідні при вирішенні різних водогосподарських завдань. Generalization of hydrometric information allows to obtain the calculated ratios to determine the hydrological characteristics of the rivers in the absence of observations on them. In the water mode of the rivers there are several characteristic phases. So for a long period of low-water phase that occurs annually in the same season due to the reduction of power of rivers is called low water. The low-water period is characterized by mean annual minimum flow during the day and in 30 days, and the frequency of its manifestation in particular periods of the year. A study of the variation of river flow is an important task in hydrology. The article describes the calculation of the ratio for a frequency of 30 daily minimum water flow for rivers in the southern coast of Crimea in the absence of historical records. If you know the frequency of existence of 30 daily minimum flow of water in any site of the river, at another target, this value can be determined by recalculation using the suggested ratios. Such calculations are necessary for solving various water problems.